Research on instruction and assessment of the new literacies of online reading comprehension - Donald J. Leu; Laurie A. Henry; Jill Castek; Douglas K. Hartman; Laurie A. Henry; David Reinking (Comprehension Instruction : Research-based Best Practices, 2008)
The Internet has rapidly become the defining medium for information, communication, and reading comprehension in the twenty-first century (Friedman, 2005; Partnership for 21st Century Skills, 2004; 2006; The New Literacies Research Team, 2007). Moreover, research indicates that online reading comprehension is not isomorphic with offline reading comprehension; proficient readers offline are not always proficient readers online (Coiro, 2007; Leu, Zawilinski, Castek, Banerjee, Housand, Liu, & O’Neil, in press). Additional reading comprehension skills are required to be a successful online reader (Castek, Leu, Coiro, Gort, Henry, & Lima, in press; Coiro & Dobler, 2007; Henry, 2006; Leu, Castek, Hartman, Coiro, Henry, Kulikowich, & Lyver, 2005). The emergence of new online reading comprehension skills has profound consequences for instruction as reading has moved from page to screen. These new literacies have redefined many aspects of traditional comprehension instruction. In this chapter, we will explore onli e reading comprehension, instruction, and assessment. The chapter will: • provide data to establish that the Internet is now a central context for reading comprehension; • define the new literacies of online reading comprehension and review research in this area; • define the emerging outlines of Internet Reciprocal Teaching (IRT), an instructional model used to teach online reading comprehension; • explore emerging assessment practices in online reading comprehension; • identify key public policy and research questions to direct upcoming work; and • describe what classroom instruction in the new literacies of online reading
Keywords: compétences; compréhension; lecture numérique